Characterization of campylobacter isolates from a South African population - Thobela, Mandile Samantha (My University, 2017)
In South Africa, there is a lack of national surveillance for Campylobacter. Campylobacter infections particularly those caused by Campylobacter jejuni and Campylobacter coli, cause a significant proportion of all diarrhoeal cases. Although diarrhoea caused by Campylobacter is short-lived, belligerent clinical manifestations include C. jejuni-induced Guillain-Barré Syndrome (GBS) which can cause considerable morbidity. Improvements in molecular subtyping methodologies, such as multi-locus sequence typing (MLST) and whole genome sequencing (WGS) based applications have been successfully applied in the field of molecular epidemiology of Campylobacter. Our study proposed to improve the molecular epidemiological understanding of Campylobacter in South Africa using polymerase chain reaction (PCR), WGS, and MLST. Antimicrobial susceptibility profiles of Campylobacter were also investigated. Furthermore, the prevalence of Campylobacter in stool specimens of children (<5 years) with acute diarrhoea and from patients with symptoms of acute flaccid paralysis (AFP) was investigated. A multiplex real-time PCR targeting C. jejuni and C. coli was used to screen a total of 2,341 samples from clinical isolates and clinical specimens associated with various existing surveillance programs. Antimicrobial susceptibility was performed using the Etest method. C. jejuni isolates were further subtyped using MLST based on the analysis of WGS data. In all surveillance programs, C. jejuni was the most predominant species of Campylobacter detected (>77%). Isolates had low prevalence of antimicrobial resistance to erythromycin (10%) and azithromycin (14%), however, ciprofloxacin (53%) and tetracycline (53%) resistance was notable. It was male (54%) children of less than five years of age (35%) who were more frequently associated with campylobacteriosis. A total of 33 different sequence types (STs) were identified through MLST; ST-227 and ST-572 were the most common STs. A total of five different clonal complexes grouped all typable isolates, with ST-206 complex and ST-21 complex being the most common clonal complexes. Strains with new unassigned STs of novel combinations of known alleles (n=8) and novel alleles were identified (n=1). Multiplex real-time PCR proved effective to detect and discriminate Campylobacter species. C. jejuni was the most isolated species during the course of the study. The application of MLST reflected the genetic diversity that exists in C. jejuni strains. The current underrepresentation of Campylobacter burden of disease in South Africa may improve if better diagnosis and surveillance are introduced in South Africa.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, South Africa, in fulfillment of the requirements for the degree, Master of Science in Medicine Johannesburg, 2017
Keywords: Campylobacter